SIMPLE METHOD FOR CALCULATION HEXAGONAL LATTICE PARAMETERS (A AND C) SYSTEM OF ZNO NANOROD VIA X-RAY ANALYSIS: REVIEW - Abdulelah, Haider (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: Zinc oxide (ZnO) nanorods, a cornerstone of one-dimensional semiconductor nanostructures, have attracted profound research interest due to their unique combination of piezoelectricity, wide bandgap, and biocompatibility. While often treated as a wurtzite-structured constant, the lattice parameters (a, b, and c) of ZnO nanorods are not immutable. This review comprehensively examines the intentional engineering of ZnO nanorod lattice constants through various synthesis strategies, including doping with foreign elements, manipulation of growth parameters, and substrate-induced strain. Method: We delve into the fundamental mechanisms—such as ionic radius mismatch, formation of intrinsic point defects, and external stress—that lead to lattice expansion or contraction. Results: The consequential tuning of functional properties, most notably the bandgap via strain-induced piezoelectric effects, is critically analyzed. Furthermore, this review consolidates recent advancements demonstrating how precise lattice control enhances performance in applications ranging from piezotronics and optoelectronics to catalysis and sensing. Novelty: By synthesizing findings from a vast body of literature, this review aims to serve as a foundational guide for researchers seeking to exploit lattice engineering as a powerful tool for tailoring ZnO nanorods for next-generation technologies.